NMFNA: A Non-negative Matrix Factorization Network Analysis Method for Identifying Modules and Characteristic Genes of Pancreatic Cancer - Ding, Qian; Sun, Yan; Shang, Junliang; Li, Feng; Zhang, Yuanyuan; Liu, Jin-Xing (Frontiers in Genetics, 2021)
Pancreatic cancer (PC) is a highly fatal disease, yet the causes of which remain unclear. Comprehensive analysis of different types of PC genetic data plays a crucial role in understanding its pathogenic mechanisms. Currently, Non-negative Matrix Factorization (NMF) based methods are widely used for genetic data analysis. Nevertheless, it is a challenge for them to integrate and decompose different types of genetic data simultaneously. In this paper, a Non-negative Matrix Factorization Network Analysis method, NMFNA, is proposed, which introduces a graph regularized constraint to the NMF, for identifying modules and characteristic genes from two-type PC data of methylation (ME) and copy number variation (CNV). Firstly, three PC networks, i.e., ME network, CNV network, and ME-CNV network, are constructed using the Pearson correlation coefficient. Then, modules are detected from these three PC networks effectively due to the introduced graph regularized constraint, which is the highlight of the NMFNA. Finally, both gene ontology and pathway enrichment analyses are performed, and characteristic genes are detected by the multi-measure score, to deeply understand biological functions of PC core modules. Experimental results demonstrated that the NMFNA facilitates the integration and decomposition of two types of PC data simultaneously, and can further serve as an alternative method for detecting modules and characteristic genes from multiple genetic data of complex diseases.